Acute injuries and chronic pathology of the head and face sustained while surf board riding. (July 2014) - Dimmick, Simon; Gillett, Mark; Sheehan, Patrick; Sutton, Cameron; Anderson, Suzanne E
The aim of the study was to identify the mechanisms and spectrum of injuries sustained to the head and face in surfboard riders, requiring presentation to an emergency department. A retrospective case series was undertaken from January 2008 to April 2012 at a tertiary hospital on the North Shore of Sydney. Twenty-nine patients were included, 26 with acute injuries and 3 with chronic pathologies. Fifteen patients (58%) had been struck in the head by their own board – 9 (60%) suffered facial bone fractures. Contact with the surfboard was the cause of facial bone fracture in 100% of cases. One patient struck by their own board ruptured their globe. Chronic/progressive deafness was the indication for undertaking imaging in three patients. Hundred percent had bilateral exostoses of the external auditory canal (surfers ear). Head and facial injuries are a significant and potential risk of surfboard riding. It is envisaged that greater knowledge of the spectrum and mechanisms of injuries sustained by surfers will drive surfboard and surfing accessory design and increase public awareness to minimise the risk of injury in the future.